Dynamic Flow Treatment of Monoethanolamine (MEA) Wastewater Using Activated Carbon, Chitosan and Rice Husk - Noor Adilah, Md Salehan; Mohd Najib, Razali; Nurul Asmawati, Roslan (2014)
This paper presents the performance of activated carbon, chitosan and rice husk in treating monoethanolamine (MEA) wastewater in order to evaluate the feasible method for recycle and reuse the MEA in the carbon dioxide (CO2) removal unit without affecting the amine concentration. This study focusing on the adsorption performance of activated carbon, chitosan and rice husk by varying the adsorbent dosage and circulation time.